THE POLISH-UKRAINE RIVALRY IS IN THE SYSTEM OF EMPLOYMENT AND HOUSING IN CITIES AND TOWNSHIPS OF GALICIA IN THE LAST THIRD XIX – AT THE BEGINNING OF XX ITEM - Вітенко, М. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In this article an author analyses influence of socio-economic factors on the Polish-Ukraine mutual relations in Galicia. The special attention is taken the problems of deficit of habitation, competition at the market of labour, social defence of habitants of cities of region. An author uses a term the “parallel worlds” for determination of etnic-religions associations between which actually and there were peracute socio-economic disputes related also to the religious and national factors.